Is It Government Duty to Ensure Cybersecurity for Citizens? Empirical Evidence from Poland - Grzegorz STRUPCZEWSKI (Communications of International Proceedings, 2021)
Cybersecurity is an important issue when dealing with e-services of public administration (also referred to as e-government or e-administration). If unskilled, unprepared, and unaware users operate sophisticated e-administration services, their vulnerability to potential cyber-attacks rises. The population of the e-administration end-users consists of individuals representing different age, education, digital competences, computer skills, cyber risk awareness, etc. In this context, some research questions have been asked. Who should be responsible for ensuring cybersecurity and for possible negative consequences of cyber incidents? The government? To what extent should the citizen himself be responsible for his cybersecurity and bear the consequences of his mistakes and negligence in using e-services? To answer them, a questionnaire survey on a sample of 808 Polish citizens has been done. It was found that most of the respondents expect the government to play leading role in providing cybersecurity for citizens and financial support in case of cyber incident, even if it could face budgetary constraints. Only 10% of respondents is ready to take responsibility for his/her own cyber security, which is relatively low value. Nevertheless, the proportion of responses differs across age group, level of education, place of living or professional status. This paper provides guidelines for policymakers in addressing cyber security needs of the citizens.
Keywords: Cybersecurity; cyber risk; policymaking; empirical research